Pengaruh Dispilin Kerja Dan Kompensasi Terhadap Kinerja Pegawai Kecamatan Sukarami Kota Palembang Dengan Motivasi Sebagai Variabel Intervening - Wulandari; Edizal; Nasir; Sari Sakarina (CV Putra Publisher, 2024)
Human resources are a critical factor in any organization’s ability to achieve its objectives. This study aims to examine the influence of work discipline and compensation on employee performance in Sukarami sub-district, Palembang City, with motivation as an intervening variable. Work discipline is assessed through punctuality, responsibility, adherence to office rules, and the use of office equipment. Compensation is evaluated based on salary, incentives, benefits, and facilities. Motivation is measured via physiological needs, safety needs, social needs, self-esteem needs, and self-actualization needs. Employee performance is quantified through work quality, work quantity, timeliness, effectiveness, and independence.This research adopts a quantitative approach, focusing on a population of 68 employees, using a saturated sampling technique. Data analysis utilized path analysis with Smart PLS 3.0 software. The findings indicate that work discipline has a positive and significant impact on work motivation, compensation has a positive and significant effect on work motivation, work discipline does not significantly affect performance, compensation significantly impacts performance, and work motivation significantly influences performance.